PERILAKU EKSPLOITASI SUMBERDAYA PERIKANAN TAKA DAN KONSEKUENSI LINGKUNGAN DALAM KONTEKS INTERNAL DAN EKSTERNAL: STUDI KASUS PADA NELAYAN PULAU SEMBILAN - Musni Lampae; Sjafri Sairin; Heddy Shri Ahimsa-Putra (Humaniora, 2005)
This article will explain the exploitative practices of Pulau Sembilan’s fishermen and their environmental consequences in internal and external contexts. Case materials utilized for the explanation are the data about dominant fishing such as collecting teripang, catching fish by dinamite and voison gained by field research. The exploitative practices are characterized by overexploitation and coral reef degradation. Contextual explanation uses the application and development of action and consequence approach with contextual mode of explanation in ecological anthropology. By applying these approach and mode, the internal/local socio-culture and the external forces (export-market situation, adoption of technological innovation, and government policies) are found as contributing to the various exploitative patterns of behaviour and their environmental consequences.